Digital curation at the university: Systematic literature review analysis with a bibliometric approach through the scopus database for the period 2012-2022 - Anas, Ansori; Salim , Tamara Adriani (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2023)
Background of the study: Universities should manage information digitally. Digital curation is a way to preserve and develop the collection of information so that it can be maintained and accessed in the future. Purpose: This study aims to determine how many studies have examined digital curation at universities from 2012-2022 and the extent of the research affiliation. Method: This research is a quantitative research using a descriptive methodology through a systematic literature review. The collection of journal articles uses bibliometric analysis to find the articles studied from the Scopus database and processed with using VosViewer to describe research trend data. Findings: There are 91 journal articles from the Scopus database on digital curation in universities from 2012 to 2022. Digital curation is the most dominant keyword with 22 events. The trend of the highest number of research shows that there are 16 journal articles in 2012. The Digital Curation keyword shows the highest number of 57 research relationship affiliations. Conclusion: This research can describe research trends, distribution map and research relationship. It can also help to show clearly that research is still rare or has not been studied to encourage novelty for the development of further research.